Light Regulation of Alternative Pre‐mRNA Splicing in Plants1. (18th January 2017) - Zhang, Hangxiao; Lin, Chentao; Gu, Lianfeng
Abstract: Alternative splicing (AS) is a major post‐transcriptional mechanism to enhance the diversity of proteome in response to environmental signals. Among the numerous external signals perceived by plants, light is the most crucial one. Plants utilize complex photoreceptor signaling networks to sense different light conditions and adjust their growth and development accordingly. Although light‐mediated gene expression has been widely investigated, little is known regarding the mechanism of light affecting AS to modulate mRNA at the post‐transcriptional level. In this minireview, we summarize current progresses on how light affects AS, and how sensory photoreceptors and retrograde signaling pathways may coordinately regulate AS of pre‐mRNAs. In addition, we also discuss the possibility that AS of the mRNAs encoding photoreceptors may be involved in feedback control of AS. We hypothesize that light regulation of the expression and activity of splicing factors would be a major mechanism of light‐mediated AS. The combination of genetic study and high‐throughput analyses of AS and splicing complexes in response to light is likely to further advance our understanding of the molecular mechanisms underlying light control of AS and plant development. Abstract : In plant, light affects alternative splicing mainly via three primary types of sensory photoreceptor pathways or retrograde signals from chloroplast, while photoreceptors themselves are also under the regulation of alternative splicing. The light regulation of splicing factors would be a major mechanism of light‐mediated alternative splicing that represents functions on dominant negative regulation, subcellular localization, or taking part in nonsense‐mediated mRNA decay pathway.